Aluminum alloy sheet for magnetic disk, aluminum alloy blank for magnetic disk, and aluminum alloy substrate for magnetic disk

The aluminum alloy plate with a specific composition addresses the challenge of achieving both rigidity and thermal deformation suppression, improving the performance and reliability of magnetic disks by enhancing rigidity and reducing vibrations.

JP2025004738AActive Publication Date: 2025-01-15KOBE STEEL LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024023206
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-26
Filing Date
2024-02-19
Publication Date
2025-01-15
Estimated Expiration
2044-02-19

AI Technical Summary

Technical Problem

Existing aluminum alloy plates for magnetic disks face challenges in achieving both good rigidity and suppressing thermal deformation during magnetic film sputtering, which affects the flatness and performance of hard disk drives.

Method used

An aluminum alloy plate with a specific chemical composition comprising Mg: 0.1-7.0% by mass, Cr: 0.005-1.0% by mass, Be: 3-100 mass ppm, Si: 0.20% by mass or less, and a total of Fe, Mn, and Ni: 0.05 to 5.9% by mass, with a Young's modulus of 70 GPa or more, a stress relaxation rate of 90% or less, and a controlled number density of intermetallic compounds, is developed to enhance rigidity and suppress thermal deformation.

Benefits of technology

The solution provides aluminum alloy plates with improved rigidity and thermal deformation suppression, ensuring high performance and reduced vibrations in thin magnetic disks, thereby enhancing the reliability of hard disk drives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025004738000002
    Figure 2025004738000002
  • Figure 2025004738000003
    Figure 2025004738000003
  • Figure 2025004738000004
    Figure 2025004738000004
Patent Text Reader

Abstract

To provide an aluminum alloy sheet for a magnetic disk, an aluminum alloy sheet blank for a magnetic disk, and an aluminum alloy sheet substrate for a magnetic disk, which have good stiffness and can suppress thermal deformation during magnetic film sputtering.SOLUTION: An aluminum alloy sheet for a magnetic disk comprises 0.1-7.0 mass% of Mg, 0.005-1.0 mass% of Cr, and 3-100 mass ppm of Be, 0.20 mass% or less of Si, 0.05-5.9 mass% of the total of at least one kind selected from Fe, Mn, and Ni, and the balance of Al and impurities.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aluminum alloy plate for a magnetic disk, an aluminum alloy blank for a magnetic disk, and an aluminum alloy substrate for a magnetic disk. [Background technology]

[0002] As information becomes more digitalized and the Internet becomes more widespread, large amounts of digital data are now being handled, and this has created a demand for larger capacity hard disk drives (HDDs), particularly in data centers.To increase the capacity of HDDs, there are studies being conducted on making magnetic disks thinner, with the aim of increasing the number of magnetic disks per HDD.

[0003] However, when attempting to improve the data transfer rate by rotating the magnetic disk, particularly at a high rotation speed, the thinner the magnetic disk is, the higher the probability of occurrence of minute vibrations.

[0004] One of the means for suppressing vibration of such a thin magnetic disk is to increase the rigidity of the substrate. For example, in Patent Documents 1 and 2, in order to improve the rigidity of the substrate, a chemical composition is adopted in which at least one of Fe, Mn, and Ni is added in a specific amount to an aluminum alloy plate, thereby increasing the rigidity of the magnetic disk substrate itself.

[0005] Furthermore, for substrates for magnetic disks, the index of "flatness" is extremely important since it greatly affects the performance of hard disk drives (HDDs) using the substrate. In the production process of substrates, there is concern about deformation due to thermal strain. This deformation adversely affects the flatness of the substrate and may lead to the production of non-standard products. Currently, in light of resource depletion, recycling of various things is progressing, and recycling of metals, which are consumed in large quantities, has been carried out for some time. The above non-standard products can also be reused through recycling, but it is essential to suppress the generation of non-standard products by suppressing thermal distortion. For example, Patent Document 3 describes an aluminum alloy plate for magnetic disks that has a specific chemical composition, a gradient in the number of compounds in the plate thickness direction that is equal to or greater than a specific value, and is excellent in flatness.

[0006] Here, as shown in Patent Document 4, it is known that in a magnetic disk substrate, thermal expansion that occurs during magnetic film sputtering causes thermal distortion around the gripping portion. Therefore, in order to obtain a magnetic disk with excellent flatness, it is necessary to suppress deformation of the magnetic disk substrate due to thermal distortion.

[0007] From the viewpoint of suppressing deformation due to thermal strain, for example, Patent Document 5 describes that by making an aluminum alloy sheet for a cap have a specific chemical composition and have a specific value or more of a difference in yield strength in a direction parallel to rolling before and after heat treatment, excellent stress relaxation resistance can be exhibited and thermal deformation can be suppressed. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Patent No. 7132289 [Patent Document 2] Patent No. 6684139 [Patent Document 3] JP 2023-004878 A [Patent Document 4] Patent Publication No. 2022-010156 [Patent Document 5] Patent Publication No. 2021-011621 Summary of the Invention [Problem to be solved by the invention]

[0009] Thus, in an aluminum alloy sheet for a magnetic disk, both good rigidity and suppression of thermal deformation are important, but there is still room for further study on an aluminum alloy sheet for a magnetic disk that satisfies both of these requirements.

[0010] The present invention has been made in consideration of the above problems, and has an object to provide an aluminum alloy plate for magnetic disks, an aluminum alloy plate blank for magnetic disks, and an aluminum alloy plate substrate for magnetic disks, which have good rigidity and can suppress thermal deformation during magnetic film sputtering. [Means for solving the problem]

[0011] As a result of extensive research, the inventors discovered that by using a specific alloy composition, it is possible to obtain an aluminum alloy plate for magnetic disks that has good rigidity and can suppress thermal deformation during magnetic film sputtering, and thus created the present invention.

[0012] That is, the present invention relates to the following. [1] Mg: 0.1~7.0% by mass, Cr:0.005~1.0% by mass, Be: 3 to 100 mass ppm; Si: 0.20 mass% or less, A total of at least one of Fe, Mn, and Ni: 0.05 to 5.9 mass%; An aluminum alloy plate for magnetic disks, the balance of which is aluminum and impurities. [2] The Fe: 0 to 1.00 mass% The Mn: 0 to 1.4 mass %, and The aluminum alloy sheet for magnetic disks according to [1], containing at least one of the Ni: 0 to 3.5 mass %. [3] The aluminum alloy sheet for magnetic disks according to [1] or [2], further comprising at least one of Cu: 1.0 mass % or less and Zn: 1.0 mass % or less. [4] The number density of intermetallic compounds on the surface with a maximum length of 0.05 μm or more and 0.33 μm or less is 1.0 × 10 6 pieces / mm 2The aluminum alloy sheet for magnetic disks according to [1] or [2] above. [5] The aluminum alloy sheet for magnetic disks according to [1] or [2], having a Young's modulus of 70 GPa or more. [6] The aluminum alloy sheet for magnetic disks according to [1] or [2], having a stress relaxation rate of 90% or less. [7] An aluminum alloy blank for magnetic disks obtained from the aluminum alloy plate for magnetic disks according to [1] or [2]. [8] An aluminum alloy substrate for magnetic disks obtained from the aluminum alloy blank for magnetic disks described in [7]. Effect of the Invention

[0013] According to the present invention, it is possible to provide an aluminum alloy plate for magnetic disks, an aluminum alloy plate blank for magnetic disks, and an aluminum alloy plate substrate for magnetic disks, which have good rigidity and can suppress thermal deformation during magnetic film sputtering. [Brief description of the drawings]

[0014] [Figure 1] 1(a) and 1(b) are diagrams for explaining the measurement of the stress relaxation rate in the examples. [Diagram 2] FIG. 2 is a diagram showing a COMPO image (magnification: 10,000 times) obtained by photographing the aluminum alloy blank No. 1 in the example using a scanning electron microscope (FE-SEM). [Diagram 3] FIG. 3 is a diagram showing a COMPO image (magnification: 10,000 times) obtained by photographing the aluminum alloy blank No. 3 in the example using a scanning electron microscope (FE-SEM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] An aluminum alloy plate for magnetic disks, an aluminum alloy blank for magnetic disks, and an aluminum alloy substrate for magnetic disks according to one embodiment of the present invention will be described below. In the following description, the aluminum alloy plate for magnetic disks, the aluminum alloy blank for magnetic disks, and the aluminum alloy substrate for magnetic disks according to this embodiment may be referred to simply as the "aluminum alloy plate," the "blank," and the "substrate," respectively.

[0016] [Aluminum alloy plates for magnetic disks] The aluminum alloy plate for magnetic disk according to the present embodiment contains 0.1-7.0 mass% Mg, 0.005-1.0 mass% Cr, 3-100 mass ppm Be, 0.20 mass% or less Si, 0.05-5.9 mass% total of at least one of Fe, Mn and Ni, with the balance being Al and impurities. The aluminum alloy plate for magnetic disk according to the present embodiment may also contain Cu and Zn. Hereinafter, each component of the aluminum alloy plate for magnetic disk according to this embodiment will be described in detail.

[0017] (Mg: 0.1 mass% or more and 7.0 mass% or less) Mg is an essential constituent element in the aluminum alloy plate for a magnetic disk according to this embodiment, and is contained in the aluminum alloy plate in order to obtain good yield strength. If the Mg content in the aluminum alloy plate is less than 0.1% by mass, the above effect cannot be obtained. On the other hand, if the Mg content in the aluminum alloy plate is more than 7.0% by mass, the rigidity decreases. Therefore, the Mg content is set to 0.1% by mass or more and 7.0% by mass or less. From the viewpoint of improving the yield strength, the Mg content is preferably 0.5 mass% or more, 1.0 mass% or more, 1.5 mass% or more, 1.7 mass% or more, 2.0 mass% or more, 2.2 mass% or more, or 2.5 mass% or more. From the viewpoint of suppressing a decrease in rigidity, the Mg content is preferably 6.5 mass% or less, 6.0 mass% or less, 5.5 mass% or less, 5.0 mass% or less, 4.5 mass% or less, 4.0 mass% or less, or 3.5 mass% or less.

[0018] (Cr: 0.005 mass% or more and 1.0 mass% or less) Cr is an essential constituent element in the aluminum alloy plate for a magnetic disk according to this embodiment, and is contained in the aluminum alloy plate in order to obtain good yield strength. If the Cr content in the aluminum alloy sheet is less than 0.005% by mass, the above effect cannot be obtained. On the other hand, if the Cr content exceeds 1.0% by mass, the intermetallic compounds become coarse and edge cracks occur, which may reduce the rollability. Therefore, the Cr content is set to 0.005% by mass or more and 1.0% by mass or less. From the viewpoint of improving the yield strength, the Cr content is preferably 0.01 mass% or more, 0.03 mass% or more, 0.05 mass% or more, 0.08 mass% or more, or 0.1 mass% or more, and from the viewpoint of ensuring rollability, the Cr content is preferably 0.9 mass% or less, 0.8 mass% or less, 0.7 mass% or less, 0.6 mass% or less, 0.5 mass% or less, 0.4 mass% or less, 0.3 mass% or less, or 0.2 mass% or less.

[0019] (Be: 3 mass ppm or more and 100 mass ppm or less) Be is an essential element in the aluminum alloy plate for magnetic disks according to this embodiment, and has the effect of forming an oxide film during casting to suppress the formation of Mg oxides. It also has the effect of improving the hot rolling property and formability of the aluminum alloy, and further has the effect of weakening the adhesion between blanks by suppressing oxidation during corrective annealing, and suppressing the deterioration of flatness due to external force during subsequent peeling, thereby making the flatness excellent. If the Be content is less than 3 ppm by mass, the effect of adding Be cannot be fully obtained. On the other hand, if the Be content exceeds 100 ppm by mass, the compounds containing Be become coarse, which may cause edge cracks and reduce rollability. Therefore, the Be content is set to 3 ppm by mass or more and 100 ppm by mass or less. From the viewpoint of fully obtaining the above-mentioned effect of the addition of Be, the content of Be is preferably 4 ppm by mass or more, 5 ppm by mass or more, 8 ppm by mass or more, or 10 ppm by mass or more, and from the viewpoint of ensuring rollability, the content of Be is preferably 80 ppm by mass or less, 50 ppm by mass or less, 30 ppm by mass or less, or 20 ppm by mass or less.

[0020] (Si: 0.20% by mass or less) Silicon is usually mixed into aluminum alloys as an inevitable impurity in ingots, and forms simple silicon or Al-Fe-Si intermetallic compounds. If the silicon content exceeds 0.20 mass%, the Young's modulus decreases, the simple silicon or Al-Fe-Si intermetallic compounds become coarse, and the rollability decreases. Therefore, the silicon content is set to 0.20 mass% or less (including 0.00 mass%). In addition, from the viewpoint of suppressing the deterioration of Young's modulus and rollability, the content of Si is preferably 0.18 mass% or less, 0.15 mass% or less, 0.13 mass% or less, 0.10 mass% or less, 0.08 mass% or less, 0.05 mass% or less, 0.04 mass% or less, 0.03 mass% or less, or 0.02 mass% or less. The lower the content of Si, the more desirable it is, and even if it is 0 mass%, the characteristics of the present invention are not impaired, but high purity raw materials (such as Al ingot and intermediate alloy ingot) are required, which increases the cost. Therefore, the content of Si is preferably 0.004 mass% or more from an industrial standpoint.

[0021] (Total of Fe, Mn, and Ni: 0.05 to 5.9 mass%) Fe, Mn and Ni are components that contribute to improving rigidity and stress relaxation resistance. Therefore, the aluminum alloy plate for magnetic disk according to this embodiment contains at least one selected from the group consisting of Fe, Mn and Ni. That is, Fe, Mn or Ni may be contained alone, or two of Fe and Mn, Mn and Ni, or Ni and Fe may be contained, or all of Fe, Mn and Ni may be contained, and there is no particular limitation as long as the total content thereof is 0.05 to 5.9 mass%. In addition, the total content of Fe, Mn and Ni is preferably 0.10 mass% or more, 0.2 mass% or more, 0.3 mass% or more, 0.5 mass% or more, 0.8 mass% or more, or 1.0 mass% or more in order to obtain good rigidity and stress relaxation resistance. On the other hand, if these are contained in excess, the compounds may become coarse and the plating property may be deteriorated. Therefore, the total content is preferably 5.5 mass% or less, 5.0 mass% or less, 4.5 mass% or less, 4.0 mass% or less, 3.5 mass% or less, 3.0 mass% or less, 2.5 mass% or less, 2.0 mass% or less, or 1.5 mass% or less.

[0022] The aluminum alloy sheet for a magnetic disk according to this embodiment preferably contains at least one of Fe: 0 to 1.00 mass %, Mn: 0 to 1.4 mass %, and Ni: 0 to 3.5 mass %.

[0023] (Fe: 1.00% by mass or less) Fe is contained in the aluminum alloy sheet to obtain good rigidity and stress relaxation resistance. On the other hand, if the Fe content in the aluminum alloy sheet exceeds 1.00 mass%, the compound may become coarse and the plating property may be deteriorated. Therefore, the Fe content is set to 1.00 mass% or less (including 0 mass%). From the viewpoint of suppressing deterioration of plating property, the Fe content is preferably 0.90 mass% or less, 0.80 mass% or less, 0.70 mass% or less, 0.60 mass% or less, or 0.50 mass% or less. From the viewpoint of obtaining good rigidity and stress relaxation resistance, the Fe content is preferably 0.01 mass% or more, 0.02 mass% or more, 0.05 mass% or more, 0.10 mass% or more, 0.15 mass% or more, 0.25 mass% or more, 0.30 mass% or more, 0.35 mass% or more, or 0.40 mass% or more.

[0024] (Mn: 1.4% by mass or less) Mn is contained in the aluminum alloy sheet to obtain good rigidity and stress relaxation resistance. On the other hand, if the Mn content in the aluminum alloy sheet exceeds 1.4 mass%, the compounds may become coarse and the plating property may be deteriorated. Therefore, the Mn content is set to 1.4 mass% or less (including 0 mass%). From the viewpoint of suppressing deterioration of plating property, the Mn content is preferably 1.3 mass% or less, 1.2 mass% or less, 1.1 mass% or less, 1.0 mass% or less, 0.9 mass% or less, 0.8 mass% or less, 0.7 mass% or less, or 0.6 mass% or less. From the viewpoint of obtaining good rigidity and stress relaxation resistance, the Mn content is preferably 0.05 mass% or more, 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, 0.4 mass% or more, or 0.5 mass% or more.

[0025] (Ni: 3.5% by mass or less) Ni is contained in the aluminum alloy sheet to obtain good rigidity and stress relaxation resistance. On the other hand, if the Ni content in the aluminum alloy sheet exceeds 3.5 mass%, the compound may become coarse and the plating property may be deteriorated. Therefore, the Ni content is set to 3.5 mass% or less (including 0 mass%). From the viewpoint of suppressing deterioration of plating property, the Ni content is preferably 3.0 mass% or less, 2.5 mass% or less, 2.0 mass% or less, 1.5 mass% or less, 1.0 mass% or less, 0.9 mass% or less, 0.8 mass% or less, 0.7 mass% or less, 0.6 mass% or less, or 0.5 mass% or less. From the viewpoint of obtaining good rigidity and stress relaxation resistance, the Ni content is preferably 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, or 0.4 mass% or more.

[0026] (Cu: 1.0% by mass or less, Zn: 1.0% by mass or less) Cu and Zn are components that broaden the solid-liquid coexistence region and contribute to reducing the frequency of molten metal leakage during casting. In addition, they are components that have the effect of uniformly precipitating zinc in zincate treatment, and also contribute to improving plating smoothness. On the other hand, if Cu or Zn is contained in excess, the plating smoothness may be deteriorated. Furthermore, the smoothness of the electroless Ni-P plating film formed on the surface may be reduced. Therefore, it is preferable that the aluminum alloy plate for magnetic disk according to this embodiment further contains at least one of Cu: 1.0 mass % or less and Zn: 1.0 mass % or less. The Cu content is preferably 1.0 mass% or less, 0.75 mass% or less, 0.50 mass% or less, 0.35 mass% or less, 0.25 mass% or less, 0.20 mass% or less, 0.10 mass% or less, or 0.05 mass% or less from the viewpoint of suppressing deterioration of plating smoothness. Also, Cu may not be contained, but if it is contained, it is preferably 0.005 mass% or more from the viewpoint of reliably obtaining the above-mentioned effect of adding Cu. The Zn content is preferably 1.0 mass% or less, 0.75 mass% or less, 0.50 mass% or less, 0.35 mass% or less, 0.25 mass% or less, 0.20 mass% or less, 0.10 mass% or less, or 0.05 mass% or less from the viewpoint of suppressing a decrease in plating smoothness. In addition, Zn does not have to be contained, but if it is contained, it is preferably 0.005 mass% or more from the viewpoint of reliably obtaining the above-mentioned effect of adding Zn.

[0027] (balance: Al and impurities) The aluminum alloy plate according to this embodiment may contain elements other than those mentioned above as impurities depending on the selection of the melting raw material during the production of the ingot. Specific examples of impurity elements include Ti, Zr, V, B, Na, K, Ca, Pb, P, Sn, Ag, Bi, In, Ge, Sr, and Cd. Among them, Ti, Zr, and V are each regulated to 0.10 mass% or less, and B, Na, K, Ca, Pb, P, Sn, Ag, Bi, In, Ge, Sr, and Cd are each regulated to 0.05 mass% or less. As long as these elements are within this range, they do not interfere with the effects of this embodiment not only when they are contained as unavoidable impurities, but also when they are actively added, such as by intentionally increasing the blending rate of scrap containing these elements. When each element shown as an impurity element is inevitably contained (that is, when it is an unavoidable impurity), the content of each element is preferably 0.005 mass% or less, and the total content of each element is preferably 0.015 mass% or less. Furthermore, in the case of a chemical composition in which the above-mentioned Si, Fe, Mn, Ni, Cu, and Zn are not added, the content of each of these as unavoidable impurities is preferably 0.005 mass % or less.

[0028] <Young's modulus: 70GPa or more> Young's modulus is the ratio of stress to strain when a material behaves elastically, and in the present invention, it affects the occurrence of vibration when a thinned magnetic disk is rotated in a HDD. If the Young's modulus of the aluminum alloy plate is 70 GPa or more, it has high rigidity, so that the vibration of the thinned magnetic disk can be reliably suppressed. Therefore, the Young's modulus of the aluminum alloy plate for magnetic disk according to this embodiment is preferably 70 GPa or more. From the viewpoint of further suppressing the vibration of the thinned magnetic disk, the higher the Young's modulus, the more preferable it is. For example, the Young's modulus is preferably 71 GPa or more, more preferably 72 GPa or more, and even more preferably 73 GPa or more. The Young's modulus can be adjusted by adjusting the contents of Mg, Si, Fe, Mn, and Ni to the amounts described in this specification. The Young's modulus can be measured, for example, in accordance with JIS Z 2280:1993 (Method of testing Young's modulus at high temperatures for metallic materials) by preparing a test piece of 60 mm x 10 mm x 1 mm thickness with the rolling direction as the longitudinal direction, and using the test piece. Specifically, in accordance with the method prescribed by the JIS, the Young's modulus can be measured by a free resonance method in an air atmosphere at room temperature (e.g., 25°C). The test device used is preferably a JE-RT model manufactured by Nippon Technoplus Co., Ltd.

[0029] <Stress relaxation rate: 90% or less> The present inventors conducted extensive research into deformation of an aluminum alloy plate for magnetic disks during sputtering of a magnetic film, and discovered that deformation can be suppressed by improving the stress relaxation resistance. If the stress relaxation rate is 90% or less, deformation can be suppressed even when stress caused by thermal distortion during magnetic film sputtering is applied to the substrate during thinning. Therefore, the stress relaxation rate of the aluminum alloy plate for magnetic disk according to this embodiment is preferably 90% or less. From the viewpoint of further suppressing deformation of the thinned substrate, the lower the stress relaxation rate, the more preferable. For example, the stress relaxation rate is more preferably 85% or less, even more preferably 80% or less, and particularly preferably 75% or less. The lower limit of the stress relaxation rate is not particularly limited, but is, for example, 0% or more, 20% or more, 50% or more, 60% or more, or 70% or more. The stress relaxation rate can be adjusted by setting the Fe, Mn, and Ni contents as described in this specification. In addition to the above Fe, Mn, and Ni contents, the treatment conditions in the homogenization heat treatment step are set to the ranges described below, and the number density of intermetallic compounds having a maximum length of 0.05 μm or more and 0.33 μm or less is set to the ranges described below.

[0030] The stress relaxation rate can be measured as follows. A test piece with a width of 10 mm and a length of 60 mm is cut out so that the longitudinal direction is parallel to the rolling direction. Then, the span length (x) in Figure 1(a) is determined using the following formulas (2) and (3) so that the bending stress in the following formula (1) is constant, and the following test is carried out. The specimen is placed in an atmospheric furnace with a bending stress applied (as shown in Fig. 1(a)) and subjected to a heat treatment (300°C x 1 hour) simulating a magnetic film sputtering process. It is then removed from the furnace and the deformation amount a before the bending stress is removed is measured. The bending stress is then removed (as shown in Fig. 1(b)) and the deformation amount b after the bending stress is removed is measured. The ratio of the deformation amount b after removing the bending stress to the deformation amount a before removing the bending stress (b / a × 100[%]) is defined as the stress relaxation rate.

[0031] σ = M / Z (1) σ: Bending stress [N / mm 2 ] M: Bending moment [N mm] Z: Section modulus (Z [mm 3 ]=(w×t 2 ) / 6) w: Plate width [mm], t: Plate thickness [mm]

[0032] M = P × x (2) M: Bending moment [N mm] P: Tip load [N] x: span length [mm]

[0033] P = (3 × E × I × δ) / x 3 (3) P: Tip load [N] E: Young's modulus [N / mm 2] I: Moment of inertia (I [mm 4 ]=(w×t 3 ) / 12) w: Plate width [mm], t: Plate thickness [mm] δ: Deflection amount (2 [mm]) x: span length [mm]

[0034] <Number density of intermetallic compounds with a maximum length of 0.05 μm or more and 0.33 μm or less: 1.0×10 6 End> The greater the number density of intermetallic compounds in the aluminum alloy that have a maximum length of 0.05 μm or more and 0.33 μm or less, the better the stress relaxation resistance properties that can be obtained. Intermetallic compounds with a maximum length of less than 0.05 μm or more than 0.33 μm have no effect on the stress relaxation resistance properties. The number density of intermetallic compounds with a maximum length of 0.05 μm or more and 0.33 μm or less on the surface of the aluminum alloy plate for magnetic disks according to this embodiment is 1.0×10 6 pieces / mm 2 More than 1.5×10 is preferable. 6 pieces / mm 2 More preferably, 2.0×10 6 pieces / mm 2 More preferably, 2.5×10 6 pieces / mm 2 More preferably, 3.0×10 6 pieces / mm 2 More than 3.5×10 is particularly preferable. 6 pieces / mm 2 The upper limit is not particularly limited, but is, for example, 1.0×10 8 pieces / mm 2 Below, 1.0 x 10 7 pieces / mm 2 The following is the result.

[0035] Examples of intermetallic compounds include Mg-Si intermetallic compounds, Al-Fe intermetallic compounds, Al-Mn intermetallic compounds, Al-Ni intermetallic compounds, Al-Fe-Mn intermetallic compounds, Al-Fe-Ni intermetallic compounds, Al-Mn-Ni intermetallic compounds, Al-Fe-Mn-Ni intermetallic compounds, Al-Cr intermetallic compounds, Al-Ti intermetallic compounds, and Al-Zr intermetallic compounds. In this case, the subject also includes Al-Fe-Cr intermetallic compounds in which a part of the above-mentioned Al-Fe intermetallic compounds is substituted, and Al-Mn-Cr intermetallic compounds in which a part of the Al-Mn intermetallic compounds is substituted. When Cu and Zn are contained in the amounts specified in the present invention, examples of the intermetallic compounds include Al-Cu intermetallic compounds and Al-Zn intermetallic compounds.

[0036] The maximum length and number density of the intermetallic compounds can be measured as follows. The surface of the measurement sample was cut with a diamond bit to make it a mirror surface, and this surface was observed at 10,000x magnification, 6 fields of view, and an observation area of ​​0.0006 mm using an FE-SEM (JSM-7001F manufactured by JEOL Ltd., accelerating voltage 5 kV). 2 The image is photographed as a composite image, which is a composition image called a COMPO image. From the photographed COMPO image, the matrix portion, i.e., the portion that appears whiter than the parent phase, is regarded as an intermetallic compound, and their maximum length is measured using particle analysis software ImageJ (ver.1.53q). The maximum length of an intermetallic compound means the maximum value of the distance between any two points on the contour line of an intermetallic compound particle. Then, the number of intermetallic compounds that are 0.05 μm or more and 0.33 μm or less among the intermetallic compounds is counted using the particle analysis software, and the number density per unit area is calculated.

[0037] [Method of manufacturing aluminum alloy sheets for magnetic disks] Next, an example of a method for producing an aluminum alloy sheet for a magnetic disk according to this embodiment will be described. The alloy plate according to the present embodiment can be manufactured by a manufacturing method and equipment under general conditions for manufacturing an aluminum alloy plate for a magnetic disk, except for some conditions in the homogenization heat treatment step and the hot rolling step. For example, an aluminum alloy plate can be manufactured by a manufacturing method including, in this order, a casting step in which a raw material is melted and the molten aluminum alloy adjusted to a predetermined chemical composition is cast into an aluminum alloy ingot by a semi-continuous casting method or the like, a homogenization heat treatment step in which the cast aluminum alloy ingot is surface-cut and subjected to homogenization heat treatment, a hot rolling step in which the homogenization heat-treated aluminum alloy ingot is hot-rolled to obtain a hot-rolled plate, and a cold rolling step in which the hot-rolled plate is cold-rolled. Note that intermediate annealing may be performed before the cold rolling step or during the cold rolling step, as necessary. Each step will be described in detail below.

[0038] (Casting process) In the casting process, the raw materials are melted at 700 to 800° C. to produce a molten aluminum alloy, which is then preferably cast into an aluminum alloy ingot at 700 to 800° C. by a known semi-continuous casting method such as DC casting.

[0039] (Homogenization heat treatment process) In the homogenization heat treatment step, the cast aluminum alloy ingot is subjected to surface grinding and then to homogenization heat treatment. The surface grinding amount can be, for example, 2 to 40 mm per side. The homogenization heat treatment is preferably carried out by holding the aluminum alloy sheet at a temperature of 400 to 600° C. for 4 to 50 hours, from the viewpoint of adjusting the stress relaxation rate of the aluminum alloy sheet to 90% or less. Specifically, by setting the homogenization heat treatment temperature to 400°C or higher and the homogenization heat treatment time to 4 hours or higher, the generation of intermetallic compounds of 0.05 μm or more and 0.33 μm or less among the intermetallic compounds in the aluminum alloy generated in the homogenization treatment is promoted, and good stress relaxation resistance properties are obtained, and the structure can be sufficiently homogenized, so that the variation in the stress relaxation resistance properties of the obtained aluminum alloy sheet can be reduced. The homogenization heat treatment temperature is preferably 420°C or higher, 440°C or higher, 450°C or higher, 460°C or higher, 480°C or higher, 500°C or higher, or 520°C or higher. On the other hand, by setting the homogenization heat treatment temperature to 600°C or lower, it is possible to prevent the surface of the aluminum alloy ingot from melting. The homogenization heat treatment temperature is more preferably 580°C or lower, and even more preferably 540°C or lower. In addition, there is no upper limit to the time for the homogenization heat treatment, but from the viewpoint of economic efficiency in the manufacturing process, it is preferably 48 hours or less, more preferably 30 hours or less, even more preferably 24 hours or less, and particularly preferably 18 hours or less. In addition, from the viewpoint of promoting the formation of intermetallic compounds, the lower limit of the time for the homogenization heat treatment is preferably 6 hours or more, more preferably 8 hours or more, and even more preferably 10 hours or more.

[0040] (Hot rolling process) In the hot rolling step, the aluminum alloy ingot that has been subjected to the homogenization heat treatment is hot rolled to obtain a hot rolled sheet. The starting temperature of the hot rolling is preferably 490°C or higher from the viewpoint of adjusting the stress relaxation rate of the aluminum alloy sheet to 90% or less, and the finishing temperature of the hot rolling is preferably 300 to 350°C. Specifically, by setting the starting temperature of hot rolling to 480° C. or higher, the rolling load during hot rolling can be reduced, and an increase in the number of hot rolling passes can be suppressed. The starting temperature of hot rolling is more preferably 490° C. or higher, and further preferably 500° C. or higher. On the other hand, from the viewpoint of suppressing cracks during hot rolling, the starting temperature of hot rolling is preferably 550° C. or lower, and more preferably 520° C. or lower. Furthermore, the thickness of the hot-rolled sheet obtained by hot rolling can be, for example, 3 mm or less.

[0041] (Cold rolling process) In the cold rolling step, the obtained hot rolled sheet is cold rolled to obtain a cold rolled sheet. The thickness of the cold rolled sheet is, for example, preferably 0.3 to 1.3 mm, and more preferably 0.70 mm or less, 0.69 mm or less, 0.65 mm or less, 0.60 mm or less, 0.55 mm or less, 0.50 mm or less, 0.45 mm or less, 0.40 mm or less, or 0.35 mm or less. By undergoing these steps in order, the aluminum alloy plate according to this embodiment can be obtained.

[0042] [Aluminum alloy blanks for magnetic disks] The aluminum alloy blank for magnetic disk according to this embodiment is obtained from the aluminum alloy plate for magnetic disk. Specifically, the blank can be manufactured by further undergoing, in this order, a punching process in which the aluminum alloy plate obtained after the cold rolling process is punched into an annular shape, and a correction annealing process in which the annular substrate obtained in the punching process is subjected to correction annealing, for example, while applying a load, to flatten it. The chemical composition of the resulting blank will not change from the aluminum alloy plate described above and will have the same composition. Moreover, each characteristic value of the blank, such as Young's modulus, stress relaxation rate, number density of intermetallic compounds, etc., is equivalent to each characteristic value of the aluminum alloy sheet. Therefore, the characteristic values ​​obtained for the aluminum alloy sheet can be regarded as the characteristic values ​​of the blank. Conversely, the characteristic values ​​obtained for the blank can also be regarded as the characteristic values ​​of the aluminum alloy sheet.

[0043] (Punching process) In the punching process, the aluminum alloy plate may be tempered as necessary, and then punched into a circular shape so that it can be used for a substrate for a 3.5-inch HDD having an inner diameter of 24 mm and an outer diameter of 96 mm, or a substrate for a 2.5-inch HDD having an inner diameter of 19 mm and an outer diameter of 66 mm.

[0044] (Straightening annealing process) In the correction annealing step, it is preferable to stack the annular substrates by sandwiching them between spacers having a high degree of flatness, and anneal the substrates while applying a load to flatten them. The annealing temperature is set to 250 to 500° C., and the holding time can be, for example, about 3 to 5 hours. The temperature increase rate in the corrective annealing can be, for example, about 80° C. / hour on average, and is preferably no faster than 1000° C. / hour. The temperature can be decreased (cooled) by, for example, opening the door of the annealing furnace.

[0045] Regarding the temperature rise in the corrective annealing, even if the temperature is raised stepwise, the effect of this embodiment is not impaired. For example, as described in paragraphs 0068 and 0069 of Japanese Patent No. 5815153, the temperature may be raised at a plurality of heating rates, i.e., stepwise heating, such that the heating rate in a specific temperature range is a predetermined rate or a predetermined rate or more and the heating rate outside the specific temperature range is a different heating rate. In this embodiment, the annealing temperature for the corrective annealing is assumed to be in the practical temperature range of 250 to 400° C. within the above-mentioned general annealing temperature range. By going through these steps in order, the blank according to this embodiment can be obtained.

[0046] [Aluminum alloy substrates for magnetic disks] The aluminum alloy substrate for magnetic disk according to this embodiment is obtained from the aluminum alloy blank for magnetic disk. Specifically, the substrate can be manufactured by carrying out a cutting process (end surface processing) for cutting the end surface of the blank and a grinding process (mirror finish) for grinding the surface (main surface) of the blank. The chemical composition of the resulting substrate will not change from the blank described above and will have the same composition. Furthermore, the characteristic values ​​of the substrate, such as Young's modulus, stress relaxation rate, and number density of intermetallic compounds, are equivalent to the characteristic values ​​of the blank. Therefore, the characteristic values ​​obtained for the aluminum alloy sheet or the blank can be regarded as the characteristic values ​​of the substrate. Conversely, the characteristic values ​​obtained for the substrate can also be regarded as the characteristic values ​​of the aluminum alloy sheet or the blank.

[0047] The aluminum alloy plate, blank and substrate according to this embodiment can be obtained by the above-mentioned method, but other processes may be performed between or before or after each process, as long as they do not adversely affect each process.

[0048] [Magnetic disk manufacturing method] The magnetic disk can be manufactured by a manufacturing method and equipment under general conditions for manufacturing magnetic disks. For example, the surface of the substrate is acid-etched to form an electroless Ni-P plating film, and then the surface of the electroless Ni-P plating film is polished. Then, a base layer, a magnetic layer, a protective film, etc. are formed on the surface of the substrate to manufacture the magnetic disk. EXAMPLES

[0049] The present invention will be specifically described below with reference to examples of the present invention, although the technical scope of the present invention is not limited thereto.

[0050] (Preparation of test materials) The test materials Nos. 1 to 3 were produced using aluminum alloys having the chemical compositions shown in Table 1 under the following conditions.

[0051] First, slabs were produced by DC casting using the molten metal in a mold with the thickness of the ingot (500 mm for No. 1 and 2, 535 mm for No. 3). Then, both sides (thickness direction) of the obtained slabs were machined by 16 mm. Then, they were subjected to homogenization heat treatment by holding at 535°C for 8 hours. Then, No. 1 and 3 were hot rolled (start temperature: about 500°C, end temperature: about 330°C) until the thickness became 2.3 mm and No. 2 until the thickness became 2.0 mm, and No. 1 was cold rolled until the thickness became 0.55 mm and No. 2 and 3 until the thickness became 0.52 mm. The blanks were then punched out to approximately 98φ using a press, then clamped between spacers and subjected to corrective annealing (heating to 200-280°C at a heating rate of 50°C / h or more, then held at 300-400°C for no more than 7 hours) to produce blanks (O-tempered material) of each thickness.

[0052] For each of the produced test materials, the number density, Young's modulus, and stress relaxation rate of the intermetallic compounds having a maximum length of 0.05 μm or more and 0.33 μm or less were evaluated as follows.

[0053] (Number density of intermetallic compounds with a maximum length of 0.05 μm or more and 0.33 μm or less) The surface of the test material was cut with a diamond bit to make it a mirror surface, and this surface was observed at 10,000x magnification, 6 fields of view, and an observation area of ​​0.0006 mm using an FE-SEM (JSM-7001F manufactured by JEOL Ltd., accelerating voltage 5 kV). 2 The image was photographed as a composite image, which is a COMPO image. From the photographed COMPO image, the matrix portion, i.e., the portion appearing whiter than the parent phase, was regarded as an intermetallic compound, and their maximum length was measured using particle analysis software ImageJ (ver.1.53q). Then, the number of intermetallic compounds having a size of 0.05 μm or more and 0.33 μm or less was counted by the particle analysis software, and the number density per unit area was calculated.

[0054] (Young's Modulus) The Young's modulus was measured in accordance with JIS Z 2280:1993 (Method of testing Young's modulus at high temperatures for metallic materials) by cutting out test pieces of 60 mm x 10 mm x thickness of the test piece in mm, with the rolling direction parallel to the longitudinal direction, from the test material. The thickness of the test piece No. 1 was 0.55 mm, and Nos. 2 and 3 were 0.52 mm. The measurements were performed using a free resonance method in an air atmosphere at room temperature (25° C.) using a test device JE-RT manufactured by Nippon Technoplus Co., Ltd. The specimens with a Young's modulus of 70 GPa or more were evaluated as "○", and those with a Young's modulus of less than 70 GPa were evaluated as "×". ○ indicates pass, and × indicates fail.

[0055] (Stress relaxation rate) Test pieces measuring 10 mm wide and 60 mm long were cut out from the test materials so that the longitudinal direction was parallel to the rolling direction. The span length (x) in Figure 1(a) was determined for each test material using the following formulas (2) and (3) so that the bending stress in the following formula (1) was constant, and the following tests were performed. The specimen was placed in an atmospheric furnace with the bending stress applied (as shown in Fig. 1(a)) and subjected to a heat treatment (300°C x 1 hour) simulating a magnetic film sputtering process. It was then removed from the furnace and the deformation amount a before the bending stress was removed was measured. The bending stress was then removed (as shown in Fig. 1(b)) and the deformation amount b after the bending stress was removed was measured. The ratio of the deformation amount b after unloading the bending stress to the deformation amount a before unloading the bending stress (b / a × 100[%]) was defined as the stress relaxation rate, and samples with a stress relaxation rate of 90% or less were rated as "O", indicating excellent deformation suppression during magnetic film sputtering, and samples with a stress relaxation rate of more than 90% were rated as "X", indicating poor deformation suppression during magnetic film sputtering.

[0056] σ = M / Z (1) σ: Bending stress [N / mm 2 ] M: Bending moment [N mm] Z: Section modulus (Z [mm 3 ]=(w×t 2 ) / 6) w: Plate width [mm], t: Plate thickness [mm]

[0057] M = P × x (2) M: Bending moment [N mm] P: Tip load [N] x: span length [mm]

[0058] P = (3 × E × I × δ) / x 3 (3) P: Tip load [N] E: Young's modulus [N / mm 2 ] I: Moment of inertia (I [mm 4 ]=(w×t 3 ) / 12) w: Plate width [mm], t: Plate thickness [mm] δ: Deflection amount (2 [mm]) x: span length [mm]

[0059] The results of evaluation of the alloy composition (chemical composition), number density of intermetallic compounds, Young's modulus, and stress relaxation rate for each test material are shown in Table 1. Note that the underlines in the table indicate that the specific features of the present invention are not met.

[0060] [Table 1]

[0061] As is clear from the results in Table 1, Nos. 1 and 2, which satisfy the provisions of the present invention, were able to obtain aluminum alloy plates and blanks having good rigidity, excellent stress relaxation resistance, and capable of suppressing thermal deformation during magnetic film sputtering. On the other hand, No. 3, in which the total amount of Fe, Mn and Ni did not satisfy the requirements of the present invention, was inferior to Nos. 1 and 2 in rigidity and stress relaxation resistance.

Claims

1. Mg: 0.1 to 7.0% by mass, Cr: 0.005 to 1.0% by mass, Be: 3 to 100 ppm by mass; Si: 0.20% by mass or less, The total of at least one of Fe, Mn, and Ni: 0.05 to 5.9 mass%, The balance of the aluminum alloy plate for magnetic disks is aluminum and impurities.

2. The Fe: 0 to 1.00 mass% The Mn: 0 to 1.4 mass%; and 2. The aluminum alloy plate for magnetic disks according to claim 1, containing at least one of the Ni: 0 to 3.5 mass %.

3. 3. The aluminum alloy sheet for magnetic disks according to claim 1, further comprising at least one of Cu: 1.0 mass % or less and Zn: 1.0 mass % or less.

4. The number density of intermetallic compounds having a maximum length of 0.05 μm or more and 0.33 μm or less on the surface is 1.0×10 6 pieces / mm 2 3. The aluminum alloy sheet for magnetic disks according to claim 1 or 2.

5. 3. The aluminum alloy sheet for magnetic disks according to claim 1, which has a Young's modulus of 70 GPa or more.

6. 3. The aluminum alloy sheet for magnetic disks according to claim 1, which has a stress relaxation rate of 90% or less.

7. 3. An aluminum alloy blank for magnetic disks obtained from the aluminum alloy plate for magnetic disks according to claim 1 or 2.

8. An aluminum alloy substrate for magnetic disks obtained from the aluminum alloy blank for magnetic disks according to claim 7.

Citation Information

Patent Citations

  • Aluminum alloy blank for magnetic disk and manufacturing method therefor, magnetic disk using aluminum alloy blank for magnetic disk and manufacturing method therefor

    JP2020029595A

  • Aluminum alloy board for magnetic disk, aluminum alloy blank for magnetic disk and aluminum alloy substrate for magnetic disk

    JP2020087485A

  • Aluminum alloy plate for magnetic disk, aluminum alloy blank for magnetic disk, aluminum alloy substrate for magnetic disk, and method of manufacturing aluminum alloy plate for magnetic disk

    JP2021093234A

  • Aluminum alloy sheet for magnetic disk, aluminum alloy blank for magnetic disk and aluminum alloy substrate for magnetic disk

    JP2023071471A

  • Aluminum alloy sheet for caps

    JP2021011621A